(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to find out and analyze the arrangement and implementation of MakassarCity Regulation No. 4 of 2013 on Non-Smoking Areas at the Muslim University of Indonesia. This research uses empirical normative research methods.The results of this study that the regulation on Non-Smoking Areas has been comprehensively regulated in the legislation. However, the implementation of such arrangements, especially at the Muslim University of Indonesia in order to follow up the Makassar City Regulation No. 4 of 2013 on Non-Smoking Areas, when viewed from legal factors, law enforcement factors, facilities or facilities factors, community factors and cultural factors are still not implemented effectively. As for theecomendasi of researchers in order for the implementation of Non-Smoking Areas in the Muslim University of Indonesia to run effectively, namely, the need for the University of Muslim Indonesia needs to comprehensively protect passive smokers by establishing special rules that bind the No Smoking Area at the Muslim University of Indonesia as a form of support for the implementation of Makassar City Regulation No. 4 of 2013 on Non-Smoking Areas. And the need for socialization and education from the makassar city government and the Indonesian Muslim University directly or indirectly about the No Smoking Area that must be applied in the place of teaching and learning process and improve the facilities and prasana so that the application of Non-Smoking Areas in the Muslim University of Indonesia can be carried out effectively. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaturan serta implementasi Peraturan Daerah kota Makassar No. 4 tahun 2013 tentang Kawasan Tanpa Rokok di Universitas Muslim Indonesia. Penelitian ini menggunakan metode penelitian normatif empiris. Hasil penelitian ini menunjukkan bahwa pengaturan mengenai Kawasan Tanpa Rokok telah diatur secara komprehensif di dalam peraturan perundang-undangan. Akan tetapi, pelaksanaan pengaturan tersebut khususnya di Universitas Muslim Indonesia dalam rangka menindaklanjuti Peraturan Daerah Kota Makassar No. 4 Tahun 2013 Tentang Kawasan Tanpa Rokok, jika dilihat dari faktor hukum, faktor penegak hukum, faktor sarana atau fasilitas, faktor masyarakat dan faktor budaya masih belum terlaksana secara efektif. Adapun rekomendasi penelitian ini agar pelaksanaan Kawasan Tanpa Rokok di Universitas Muslim Indonesia berjalan efektif yaitu, perlunya pihak Universitas Muslim Indonesia perlu melakukan perlindungan terhadap perokok pasif secara komprehensif dengan cara membentuk aturan khusus yang mengikat mengenai Kawasan Tanpa Rokok di Universitas Muslim Indonesia sebagai bentuk dukungan implementasi Peraturan Daerah Kota Makassar No. 4 Tahun 2013 Tentang Kawasan Tanpa Rokok. Dan perlunya sosialisasi serta edukasi dari pemerintah kota Makassar serta pihak Universitas Muslim Indonesia secara langsung maupun tidak langsung mengenai Kawasan Tanpa Rokok yang wajib diterapkan di tempat proses belajar mengajar serta meningkatkan sarana dan prasana agara penerapan Kawasan Tanpa Rokok di Universitas Muslim Indonesia dapat terlaksana dengan efektif.